EEG inter/intra-hemispheric coherence and asymmetric responses to visual stimulations. - Cvetkovic D; Cosic I; Cvetkovic, Dean; Cosic, Irena (Medical & Biological Engineering & Computing, 2009)
This study has attempted to increase the meaning and significance of findings in the experimental areas of electroencephalographic (EEG) visual or photic driving. The aim of this study was to investigate whether the visual stimulation at particular extremely low frequency order could possibly induce changes in the corresponding EEG frequency bands by examining the functional connectedness between brain regions. This was evaluated by applying the improved experimental protocol and objective using non-parametric spectral estimation coherence algorithm. The findings from our study revealed a significantly higher coherence in the EEG beta2 band (16.6 Hz) corresponding to 16.66 Hz visual stimulation, suggesting a high inter-hemispheric functional connectivity during visual stimulus. A significant increase was revealed during 50 Hz visual stimulation at gamma band and a decrease during 4 Hz visual stimulation at theta band, linked with a substantial transitional shift in predominance from anterior to posterior relative power. This study may also increase the awareness of EEG visual driving response studies in clinical practice to uncover potential neurophysiologic abnormalities.